FACTORS RELATED TO TREATMENT SEEKING BEHAVIOR AMONG SPONDYLITIS TUBERCULOSIS PATIENTS: A SYSTEMATIC REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i2.106 - Adelina Vidya Ardiyati; Masfuri Masfuri (Alta Dharma Publisher, 2019)
Abstract Introduction: Tuberculosis is a global public health crisis. Spondylitis Tuberculos is secondary infection that caused by mycobacterium tuberculosis. Most of spondylitis TB patient come to health care facilities with complication, such as deformity and deficit neurology. Health seeking behavior allows the patients to choose their preferres healthcare destination and the best timing of health seeking will resulting a good outcome of treatment. Aim: A systematic review was carried out to understand factors related to treatment seeking behavior including health seeking behavior, related to delays and attitude regarding spondylitis tuberculosis and the services linked with it. Materials and Methods: An electronical database search strategy was adopted using Proquest, EBSCOHost, and ScienceDirect to obtain research papers in the said subjects. Of 22 articles obtained by the end of this search process 10 full text articles were finally selected for the purpose of this review. Results: Of the 10 studies identified, the results showed that some factors associated with related to treatment seeking behavior including (1) Perception of Disease and health service for Spondilitis TB; (2) Self healing and non medical treatment; (3) Knowledge and Misspperception of Spondilitis TB patient; (4) Reasons for seeking care/Delay in seeking care. Conclusion: Health seeking behavior and related delays are most importance in spondylitis TB care, because spondylitis TB requires timely treatment and protracted treatment to reach the best outcome of treatment. Required level of knowledge and positive health behavior helps the patient in taking timely help appropriate helath facility. Keywords: Help seeking behavior, Patient delay, Treatment delay, Spondilitis TB